CXCR4 allows T cell acute lymphoblastic leukemia to escape from JAK1/2 and BCL2 inhibition through CNS infiltration. Issue 5 (16th April 2021) - Walker, Kirsti L.; Rinella, Sean P.; Hess, Nicholas J.; Turicek, David P.; Kabakov, Sabrina A.; Zhu, Fen; Bouchlaka, Myriam N.; Olson, Sydney L.; Cho, Monica M.; Quamine, Aicha E.; Feils, Arika S.; Gavcovich, Tara B.; et al.
Abstract: Targeting the JAK/STAT and BCL2 pathways in patients with relapsed/refractory T cell acute lymphoblastic leukemia (T-ALL) may provide an alternative approach to achieve clinical remissions. Ruxolitinib and venetoclax show a dose-dependent effect on T-ALL individually, but combination treatment reduces survival and proliferation of T-ALL in vitro . Using a xenograft model, the combination treatment fails to improve survival, with death from hind limb paralysis. Despite on-target inhibition by the drugs, histopathology demonstrates increased leukemic infiltration into the central nervous system (CNS) as compared to liver or bone marrow. Liquid chromatography-tandem mass spectroscopy shows that ruxolitinib and venetoclax insufficiently cross into the CNS. The addition of the CXCR4 inhibitor plerixafor with ruxolitinib and venetoclax reduces clinical scores and enhances survival. While combination therapy with ruxolitinib and venetoclax shows promise for treating T-ALL, additional inhibition of the CXCR4-CXCL12 axis may be needed to maximize the possibility of complete remission.